Carbon Honeycomb High Capacity Storage for Gaseous and Liquid Species - Zubarev, Evgeniy N.; Krainyukova, Nina V. (American Physical Society, 2016)
We report an exceptionally stable honeycomb carbon allotrope obtained by deposition of vacuumsublimated graphite. The allotrope structures are derived from our low temperature electron diffraction and electron microscopy data. These structures can be both periodic and random and are built exclusively from sp2-bonded carbon atoms, and may be considered as three-dimensional graphene. They demonstrate high levels of physical absorption of various gases unattainable in other carbon forms such as fullerites or nanotubes. These honeycomb structures can be used not only for storage of various gases and liquids but also as a matrix for new composites.
Keywords: вуглецевий стільниковий накопичувач високої місткості; алотроп стільникового вуглецю; тривимірний графен; зберігання газів і рідин; carbon honeycomb; carbon allotrope; three-dimensional graphene; storage of various gases and liquids